2016
DOI: 10.1016/j.nicl.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal decrease in blood oxygenation level dependent response in cerebral amyloid angiopathy

Abstract: Lower blood oxygenation level dependent (BOLD) signal changes in response to a visual stimulus in functional magnetic resonance imaging (fMRI) have been observed in cross-sectional studies of cerebral amyloid angiopathy (CAA), and are presumed to reflect impaired vascular reactivity. We used fMRI to detect a longitudinal change in BOLD responses to a visual stimulus in CAA, and to determine any correlations between these changes and other established biomarkers of CAA progression. Data were acquired from 22 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Our findings in symptomatic mutation carriers are in line with previous reports showing similar BOLD changes after a visual stimulus in symptomatic persons diagnosed with sporadic CAA that are shown to decrease over time. 6;20;21 Using the same methods to assess the vascular reactivity as previously published, 6 we found that the BOLD response values for symptomatic HCHWA-D mutation carriers were very similar to the older sporadic CAA patients. Compared with this previous study, 6 the values we obtained in the older controls were similar, although the younger controls in our study have higher amplitude and a faster time to peak.…”
Section: Discussionsupporting
confidence: 66%
“…Our findings in symptomatic mutation carriers are in line with previous reports showing similar BOLD changes after a visual stimulus in symptomatic persons diagnosed with sporadic CAA that are shown to decrease over time. 6;20;21 Using the same methods to assess the vascular reactivity as previously published, 6 we found that the BOLD response values for symptomatic HCHWA-D mutation carriers were very similar to the older sporadic CAA patients. Compared with this previous study, 6 the values we obtained in the older controls were similar, although the younger controls in our study have higher amplitude and a faster time to peak.…”
Section: Discussionsupporting
confidence: 66%
“…34 Ex vivo studies with isolated cerebral arterioles have shown that synthetic Aβ40 (and to a lesser degree Aβ42) induced direct vessel constriction, enhanced response to vasoconstrictors, and reduced response to vasodilators. [35][36][37] These results have been reproduced in different transgenic models and in small human studies, [38][39][40][41] and have been correlated in mice with CAA severity. 42…”
Section: Pathophysiologymentioning
confidence: 59%
“…Those with CAA show a decline in BOLD amplitude that is detectable at 1 year; longitudinal difference in BOLD amplitudes was significantly lower in CAA compared with controls 26 …”
Section: Biomarkers Advances and Mechanistic Insightsmentioning
confidence: 92%